Hormonal induction of Brycon cephalus (Characiformes, Characidae) to spermiation using D-ala6, pro9net-mGnRH + metoclopramide - Bashiyo-Silva, Cristiane [UNESP]; Costa, Raphael da Silva [UNESP]; Ribeiro, Douglas de Castro [UNESP]; Senhorini, José Augusto; Veríssimo-Silveira, Rosicleire [UNESP]; Ninhaus-Silveira, Alexandre [UNESP] (Cambridge University Press, 2015)
This study aimed to establish a hormonal induction protocol for spermiation of Brycon cephalus males, using Ala6, Pro9Net-mGnRH + metoclopramide (Ovopel®). Thus, 20 males were used divided into three inductor treatments [⅓ pellet/kg (T1), ⅔ pellet/kg (T2) and 1⅓ pellet/kg (T3)] and one control group (CO), which only received physiological solution applications (0.9% NaCl). All treatments were applied in a single dose. For evaluation of the availability of the treatment, the following seminal parameters were analyzed: seminal volume, subjective spermatic motility, duration of motility, pH, osmolality and spermatic concentration. T3 showed the highest seminal volume (4.66 ± 1.52 ml), and was significantly different in comparison with T1 (2.0 ± 0.9 ml), T2 (3.5 ± 1.3 ml) and CO (2.3 ± 1.2 ml). In relation to spermatic motility, T2 and T3 showed significantly higher levels [5, (81-100%)]. However, T3 showed significantly lower average sperm motility duration than T1, T2 and CO (30 ± 7 s; 28 ± 6 s; 32 ± 8 s, respectively). With regard to the seminal parameters of spermatic concentration, pH and osmolality, no significant variation was verified among treatments. In conclusion, mGnRH + metoclopramide used for hormonal induction of B. cephalus reproduction does not induce changes related to spermatic concentration, pH and osmolality parameters of the seminal fluid and the most adequate doses among tested treatments were ⅔ pellet/kg live fish.
Keywords: Induced spawning; Neotropical fish; Semen quality; Seminal characteristics